ANALISIS HASIL DRIVE TEST MENGGUNAKAN SOFTWARE G-NET DAN NEMO DI JARINGAN LTE AREA DENPASAR - Yogi Priyandana Adi Saputra, I Gede Made; Sudiarta, Pande Ketut; Sukadarmika, Gede (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
The development of technology is connected with customer needs for the speed and stability of LTE network access. Ensuring the quality of the LTE network can be done by measuring using the drive test method in the service area. The test drive must be equipped with software such as Nemo Handy and G-Net Track Pro. Nemo Handy is a professional drive test software that is widely used by providers, while G-Net Track Pro is a drive test software that was previously applied in the learning process at the campus. So that the measurement results using Nemo Handy and G-Net Track Pro for RSRP, RSRQ and SINR parameters need to be compared to performance. From the comparison of RSRP between measurements with theoretical stated Nemo Handy measurement results are closer than G-Net Track Pro. For example, the difference between RSRP in the PURADEMAK eNodeB for Nemo Handy was 5.96 dBm and the G-Net Track Pro was 9.4 dBm. This is due to the weakness of the G-Net Track Pro device that does not have the PCI locking feature as in Nemo Handy so that at some point the measurement cannot be compared.